MODERN TECHNOLOGIES OF INCLUSIVE EDUCATION IN THE USA - Inna Stanislavovna Bessarabova (Science and Innovation Center Publishing House, 2015)
The urgency of the research is stipulated by the leading role of the inclusive education in organizing the work with schoolchildren who have alternative physical or mental development. The subject of the research is the process of education of the alternative schoolchildren in modern American school. The purpose of the research is to study the leading technologies of inclusive education in modern American school. Methods of the research are theoretical analysis of the problem in pedagogy, psychology, sociology; comparative analysis and classification of the approaches of American and Russian scholars concerning the definitions, goals, tasks, concepts and subject matter of multicultural education and inclusive education. The results of the research showed that there is a variety of technologies, that is why it is rational to systematize them in the following groups: pedagogical managerial technologies consider the functions of every participant of the educational process, but the teacher remains the leading coordinator of the whole process; technologies of the democratization of the social support consider the creation of the democratic atmosphere at school and community as the most important condition for the inclusive environment; service technologies of the meeting of the special educational requirements denote the providing of the necessary educational services to a child, which facilitate his inclusion into the educational environment; tutoring technologies imply the help of the tutor, whose functions include  adequation of the various children’s abilities and potential regardless of the degree of manifestation of various alternative forms. Practical implications of the results. The results of the research provide the basis for project development of the process of inclusive education in Russian educational institutions during working out of the new technologies, methods and means of education of alternative schoolchildren.